The economic way of thinking - Heyne, Paul T; Boettke, Peter J; Prychitko, David L (Boston : Pearson, 2014)
This book explains the basic principles of micro - and macroeconomic analysis and shows a method of reasoning that teaches them how to apply these principles as tools. It offers a method of reasoning to think like an economist through example and application and also shows how not to think, by exposing errors in popular economic reasoning
1. The economic way of thinking -- 2. Efficiency, exchange, and comparative advantage -- 3. Substitutes everywhere: the concept of demand -- 4. Cost and choice: the concept of supply -- 5. Supply and demand: a process of coordination -- 6. Unintended consequences: more applications of supply and demand -- 7. Profit and loss -- 8. Price searching -- 9. Competition and government policy -- 10. Externalities and conflicting rights -- 11. Markets and government -- 12. The distribution of income -- 13. Measuring the overall performance of economic systems -- 14. Money -- 15. Economic performance and real-world politics -- 16. The wealth of nations: globalization and economic growth
Includes index
Includes bibliographical references and index
Keywords: Economics